'Reality' Fiction and the Great Barrier Reef - Stephen Torre (eTropic: electronic journal of studies in the tropics, 2005)
Di Morrrissey is one of Australia's most widely-read writers of popular fiction. Her special twist on the mode is to choose a particular setting and research it deeply, often living in the area for a time. Her thirteenth novel, The Reef (Sydney: Pan Macmillan, 2004) is set on Branch Island "named because it was an island sprouting right from a limb of the Great Barrier reef (135), somewhere east of "Headland Bay" which, when described (133-34) suggests a hybrid Cairns/Cardwell/Port Douglas, actual towns spread along Australia's North Queensland coast, which is paralleled by the Great Barrier Reef.